Principle of construction of system controlling complexes of technical protection of in-formation in digital commutative communication systems - Чуприн, В. М.; Конахович, Г. Ф.; Потапов, В. Г.; Сухопара, А. Н. (Proceedings of National Aviation University (archive), 1999)
Considered is the principle of construction of systems controlling complexes of technical protection means of information in order to maintain the present level of protection of information resources in digital commutative communication systems. Adaptive scheme of controlling such complexes is proposed